2013
DOI: 10.2500/ajra.2013.27.3881
|View full text |Cite
|
Sign up to set email alerts
|

Nasal Eosinophilia and Serum Soluble Intercellular Adhesion Molecule 1 in Patients with Allergic Rhinitis Treated with Montelukast Alone or in Combination with Desloratadine or Levocetirizine

Abstract: The improvement of nasal symptoms in patients with AR treated with antihistamines, with or without montelukast, may additionally result from the reduction of sICAM-1 and nasal eosinophilia. Because the combination therapy may bring inconclusive benefits in this area there is a strong need of further studies to find mechanisms that favor combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
3
14
0
Order By: Relevance
“…There are also in vivo studies that revealed the anti-inflammatory effect of H1 antihistamines. Both desloratadine and levocetirizine reduced ICAM-1 and nasal Eo [ 44 ], similar to present results. In the present study, VCAM-1 was not reduced by AH1, only ICAM-1 and E-selectin.…”
Section: Discussionsupporting
confidence: 91%
“…There are also in vivo studies that revealed the anti-inflammatory effect of H1 antihistamines. Both desloratadine and levocetirizine reduced ICAM-1 and nasal Eo [ 44 ], similar to present results. In the present study, VCAM-1 was not reduced by AH1, only ICAM-1 and E-selectin.…”
Section: Discussionsupporting
confidence: 91%
“…Our study results, thus, support other earlier studies [6,7,17] which evaluated the anti-allergic effect of various antihistamines and their combination with montelukast in AR. In these [12,13] studies, along with subjective symptoms, objective evidence of anti-allergy such as domiciliary nasal peak flow, nasal eosinophilia, and serum soluble intracellular adhesion molecule were also measured, and individual antihistamines had upper hand over their combinations with montelukast.…”
Section: Discussionsupporting
confidence: 83%
“…To contradict this finding, many comparative studies in AR patients have concluded that individual antihistamines such as fexofenadine, loratadine, [12] and desloratidine [7,13] are as effective as their combinations with montelukast, thus not justifying the various fixed-dose combinations (FDC) of antihistamines with montelukast available in market. Literature survey also revealed that comparative studies of other antihistamines in AR such as ebastine, a secondgeneration drug, with its combination with montelukast are very much scanty.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The contained ginsenosides can exert a controlled glucocorticoid-like effect. 29,30 Safety issues associated with long-term administration of KRG should be considered. A multicenter, double-blind, randomized, placebo-controlled trial, involving 100 patients and conducted over a 24-week period, revealed no significant differences in adverse events between KRG and placebo groups.…”
Section: Discussionmentioning
confidence: 99%